Rabindranath Tagore and fifty years of Sahitya Akademi - Biswajit Sinha (Delhi : Eastern Book Linkers, 2006)
Articles on the influence of Rabindranath Tagore, 1861-1941, Bengali author, on the publishing activities, seminars, and awards initiated by Sahitya Akademi, the Academy of Letters of India, for the last fifty years.
Keywords: Indic literature; Sahitya Akademi; Rabindranath Tagore; Literature Tagore Study; Literature Bengali Study; Literature Bengali; Literature